Evaluation of a BLDC drive line and energy analysis for an electric Ultra Light Vehicle - Collings, William (My University, 2011)
To achieve a better understanding of the vehicle a test bench was built using the same battery, controller and motor as the vehicle. With this test bench tests were conducted so that efficiency for the controller and motor could be measured for different speeds and torques. The result of this measurement gives an indication that the motor should preferably be driven at a speed between 250-600 rpm to achieve the highest efficiency. After the efficiency for the motor and controller was known it was used in a simulation model to estimate energy usage for the whole vehicle. When all parameters and variables was gathered several simulations was run. All simulations where run with the ECE-15 drive cycle since this is commonly used in the automotive industry and also makes it easier to compare the results with other vehicles. The result from each simulation, given in section 0, is shown with three values; energy usage [Wh/km], drivability [%] and distance [km]. Drivability is a comparison between the vehicles speed and the speed given by the ECE-15 drive cycle. If the vehicle speed doesn’t match the drive cycle speed, due to motor limitation, its ability to perform isn’t fully satisfied and this indication is given by its value of drivability. Distance is how far the vehicle can go with the given parameters and energy usage is basically how much energy the vehicle would consume per kilometer for the ECE-15 drive cycle. It is rather obvious that adding weight or having a different air drag coefficient and rolling resistance will affect the vehicle’s performance and energy usage. But it’s also noticeable how the battery’s inner resistance or changing the auxiliary power, mostly consisting of lights, will also affect the energy consumption. Decreasing the inner resistance with 40mΩ and reducing auxiliary power with 50W will almost give an additional 6km driving distance. All simulations are based on a case setup, given in section 4.13, which gives the values of 47.5Wh/km, 99.96% drivability and a distance of 28.58km. Since the vehicle is very light an increase of 2 passengers will change the values to 65.7Wh/km, 98.71% drivability and 20.68km.
Keywords: Elkraftteknik; Electric power engineering